2015
DOI: 10.1111/vox.12272
|View full text |Cite
|
Sign up to set email alerts
|

Buffy coat (top/bottom)‐ and whole‐blood filtration (top/top)‐produced red cell concentrates differ in size of extracellular vesicles

Abstract: Haemolysis and EVs increase in BC and WBF RCCs during storage. Differences in the size characteristics of the EVs in WBF and BC RCCs suggest that non-RBC EVs are more prevalent in WBF products. Understanding the impact that manufacturing has on the characteristics of the different populations of EVs in RCCs will aid quality improvement efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 17 publications
5
46
0
Order By: Relevance
“…It has been indicated that RBC membrane changes occur ex vivo and that there is a reduction in ATP and an increase in percent hemolysis, which are clearly associated with RBC membrane changes and microvesiculation [31,51,56,57,58]. This supports our findings that a positive correlation between EVs and hemolysis and a negative correlation between EVs and the level of ATP or deformability parameters (El max ) were observed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It has been indicated that RBC membrane changes occur ex vivo and that there is a reduction in ATP and an increase in percent hemolysis, which are clearly associated with RBC membrane changes and microvesiculation [31,51,56,57,58]. This supports our findings that a positive correlation between EVs and hemolysis and a negative correlation between EVs and the level of ATP or deformability parameters (El max ) were observed.…”
Section: Discussionsupporting
confidence: 92%
“…It has been suggested that the characteristics of EVs can vary among the blood products due to the variation in the blood processing methods [51,52]. An article by Bakkour et al [19] highlighted some feasible reasons to explain the variation in EV characteristics between RCF and WBF RCCs, including variability in the temperature and the lengths of pre-processing storage time as well as leukoreduction technique.…”
Section: Discussionmentioning
confidence: 99%
“…3), suggesting that in the RCCs there was a mixture of exosomes (50-100 nm) and plasma membrane microvesicles (ectosomes, 200-250 nm) changing in proportion during storage [20], which is consistent with the accumulation of RBC EVs (ectosomes) during storage (fig. 1).…”
Section: Resultsmentioning
confidence: 71%
“…Flow cytometry and the use of Trucount tubes (BD Biosciences, San Jose, CA, USA) for glycophorin A-positive (CD235a+) extracellular vesicle (EV) quantification was performed as elsewhere described [19,20]. Briefly, RBCs were sampled from the units, and 5 µl were diluted with HEPES Ca 2+ (2.5 mmol/l) buffered saline, pH 7.4, mixed with 5 µl each anti-CD235a fluorescein isothiocyanate (FITC), anti-CD47 phosphatidylethanolamine (PE) and Annexin V-APC, and transferred to Trucount tubes (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation